2021
DOI: 10.1097/brs.0000000000004046
|View full text |Cite
|
Sign up to set email alerts
|

The Demographics and Epidemiology of Infantile, Juvenile, and Adolescent Idiopathic Scoliosis in a Southern California Integrated Health Care System

Abstract: Study Design. Prognostic study, Level III. Objectives. The aim of this study was to determine the incidence and demographics of idiopathic scoliosis (IS) in a large cohort of children in a Southern California integrated healthcare system, and to identify the demographic or clinical factors associated with the greatest risk of IS. Summary of Background Data. Although many authors have reported on the incidence and prevalence of IS in children, there have been few incidence studies in the United States on large,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…The association between race and ethnicity and the severity of the spinal curve severity as measured by Cobb angles varies greatly between studies. One study showed that Hispanic patients had lower Cobb angles in comparison to all other races, while other studies show that Black patients had the highest Cobb angles, and other studies further showed no difference in Cobb angle severity between races [11,13,25,26]. While no definite associations between race and curve severity can be concluded, there have been notable correlations between socioeconomic factors and race that may provide an explanation for the variability in the race and IS prevalence and curve severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between race and ethnicity and the severity of the spinal curve severity as measured by Cobb angles varies greatly between studies. One study showed that Hispanic patients had lower Cobb angles in comparison to all other races, while other studies show that Black patients had the highest Cobb angles, and other studies further showed no difference in Cobb angle severity between races [11,13,25,26]. While no definite associations between race and curve severity can be concluded, there have been notable correlations between socioeconomic factors and race that may provide an explanation for the variability in the race and IS prevalence and curve severity.…”
Section: Discussionmentioning
confidence: 99%
“…The linear rank regression indicates that while the association between BMI and the Cobb proximal thoracic angle is statistically significant, BMI only explains 5% of the variability in the proximal thoracic Cobb angle. BMI has different associations with IS curve severity; some studies showing lower BMI is associated with higher Cobb angles [14,25], while others show a positive correlation between higher BMI and higher Cobb angles [27] as well as increased rates of inpatient and intraoperative complications related to IS [16,28,29]. Despite the variability in which BMI affects curve severity, both extremes in the literature suggest a correlation with increased Cobb angle and increased complication rates, which brings up nutrition as a possible contributing factor to BMI.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this, it is primarily performed through X-ray images, and it is determined that the Cobb angle is 10° or more [3,4]. Idiopathic scoliosis, which accounts for 85% of scoliosis cases, has been reported with a prevalence of 0.9% to 12% worldwide [5]. The exact cause has not been identified, and it is classified into infancy (0-3 years), juvenile (3-10 years), and adolescence (10 years or older) according to the time of expression.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative incidence estimates are 1.0% for a Cobb angle ≥ 20° and 0.4% for a Cobb angle ≥ 40°. In the study conducted by Bondar et al (Bondar, Nguyen, Vatani, & Kessler, 2021) for the adolescent group in Southern California, the incidence rate was 28.6/100,000 person-year, in which females had a greater initial curve magnitude than boys (18.1° vs. 16.7°). In China (Qiu, 2017), the incidence rate of scoliosis varied from 0.6% to 2.0%.…”
mentioning
confidence: 99%